Sexual function and metabolic/hormonal changes in women using long-term hormonal and non-hormonal contraceptives: a pilot study - Igor Fernando de Aquino Moreira; Maria Passos Bianchini; Gabrielle Rodrigues Campos Moreira; Alessandra Maciel Almeida; Bruno Almeida Rezende (BMC, 2020)
Abstract Background Female sexual dysfunction is a common condition that negatively impacts the emotional health and quality of life of the affected individuals. Long-acting reversible contraceptives (LARCs) are becoming increasingly popular due to their effectiveness and convenience. LARCs can be hormonal (etonogestrel releasing implant-ENG and Levonorgestrel intrauterine system-LNG) or non-hormonal (copper intrauterine device-CuIUD and copper-silver intrauterine device-SIUD). There are very few studies that assess the influence on LARCS on sexual function are lacking. This study aimed to assess changes in sexual function as well as metabolic and hormonal parameters in women after implantation with LARCs. Methods In this prospective cohort study, we assessed 80 women who visited the Military Police Hospital in Brazil for LARCs placement. The study participants were divided into 4 groups according to the type of LARC received: ENG n = 17; LNG n = 22, CuIUD n = 18 and SIUD n = 23. The four groups were evaluated twice (prior to LARC placement and approximately 3 months later) for sexual function, using the Female Sexual Function Index (FSFI) and Female Sexual Quotient (QS-F) questionnaires. Metabolic and hormonal parameters were also assessed using blood tests. Results ENG worsened sexual function according to FSFI and QS-F, across all domains. A decrease in sex hormone-binding globulin (SHBG) between stages was observed for all groups. We observed an improvement in sexual function for non-hormonal LARCs, specially SIUD. However this improvement was not statistically significant. Conclusion The use of non-hormonal LARCS improved sexual function. Etonogestrel implants, had a negative influence on sexual function, probably by blocking ovarian function, and thus reducing the production of androgens and estrogens.